Magnesium alloy surface high-wear-resistance micro-arc oxidation film layer and preparation method thereof
By adding nanoTiO2 particles to the electrolyte of the microarc oxide film layer on the surface of the magnesium alloy, the structure and structure are improved, and the problem of poor wear resistance of the microarc oxide film layer on the surface of the magnesium alloy is solved, and its wear resistance is significantly improved.
Patent Information
- Application Number
- CN202411846419.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
The micro-arc oxide film layer on the surface of magnesium alloy has poor wear resistance, large porosity and poor density, which affects its wear resistance.
NanoTiO2 particles were added to the electrolyte and microarc oxidation treatment was used to improve the structure, structure and performance of the microarc oxidation film layer on the surface of the magnesium alloy, thereby improving its wear resistance.
By adding nanoTiO2 particles, the porosity of the film layer is reduced, the density is improved, the wear resistance of the micro-arc oxide film layer on the surface of magnesium alloy is significantly improved, and the service life of magnesium alloy parts is extended.
Smart Images

Figure CN119663403A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of surface treatment, in particular to a high wear-resistant micro-arc oxidation film layer on the surface of a magnesium alloy and a preparation method thereof. Background Art
[0002] As a national strategic emerging industry, the magnesium alloy industry is the lightest metal structural material currently in practical application. It has the advantages of good machinability, corrosion resistance, impact resistance, dimensional stability, and easy recycling, and is used as a strategic raw material by many developed countries. However, since most of the working environments of magnesium alloys are relatively harsh, they will produce more wear and damage, so measures need to be taken to improve their wear resistance and expand their application scenarios.
[0003] Micro-arc oxidation technology is to place aluminum, magnesium, titanium and other metals in the electrolyte, and through high-voltage micro-arc discharge, on the basis of anodic oxidation, through a larger current and voltage, spark discharge is generated on the metal surface to form a ceramic film layer. It is also called plasma oxidation and anode spark deposition. The ceramic layer produced by this process, under the combined action of thermochemistry, plasma chemistry and electrochemistry, greatly increases the hardness, corrosion resistance, thermal stability and wear resistance of the alloy, and has broad application prospects.
[0004] However, although the micro-arc oxidation technology can effectively improve the corrosion resistance of magnesium alloys, its effect on improving the wear resistance of magnesium alloys is still limited. After the magnesium alloy is treated with micro-arc oxidation, although a micro-arc oxidation film is formed on the surface of the magnesium alloy, the film has a large porosity and poor density, which directly affects the wear resistance of the micro-arc oxidation film. Therefore, it is necessary to develop a preparation method that can significantly improve the wear resistance of the micro-arc oxidation film on the surface of the magnesium alloy. Summary of the invention
[0005] Aiming at the technical problem that the wear resistance of the micro-arc oxidation film on the surface of magnesium alloy is poor, the present invention provides a high wear-resistant micro-arc oxidation film on the surface of magnesium alloy and a preparation method thereof. 2 The particles are used to improve the organization, structure and performance of the micro-arc oxidation film on the magnesium alloy, thereby improving the wear resistance of the micro-arc oxidation film.
[0006] The present invention achieves the above technical objectives through the following technical means.
[0007] A method for preparing a highly wear-resistant micro-arc oxidation film on a magnesium alloy surface comprises the following steps:
[0008] S1. Pretreatment of the magnesium alloy substrate: grinding and polishing the magnesium alloy substrate, and then cleaning and drying;
[0009] S2. Prepare silicate alkaline electrolyte: At room temperature, add Na 2 SiO3 , KF and NaOH were dissolved in deionized water and ultrasonicated until completely dissolved before adding TiO 2 Nanoparticles, continue ultrasonication until TiO 2 The nanoparticles are uniformly dispersed in deionized water to obtain a silicate alkaline electrolyte;
[0010] S3. Micro-arc oxidation treatment: stainless steel is used as cathode and the pretreated magnesium alloy substrate is used as anode and placed in a silicate alkaline electrolyte. After micro-arc oxidation treatment, it is rinsed and dried to form a highly wear-resistant micro-arc oxidation film layer on the magnesium alloy sample.
[0011] Furthermore, the magnesium alloy in step S1 is AZ91D magnesium alloy.
[0012] Furthermore, in step S1, the specific steps of cleaning are: using deionized water and anhydrous ethanol to rinse the polished magnesium alloy block in sequence.
[0013] Furthermore, in the silicate alkaline electrolyte, Na 2 SiO 3 The concentration of is 5-10 g / L, the concentration of NaOH is 1-3 g / L, the concentration of KF is 0.5-2 g / L, and the concentration of TiO 2 The concentration of the nanoparticles is 2 to 8 g / L.
[0014] Furthermore, in the silicate alkaline electrolyte, Na 2 SiO 3 The concentration of is 10g / L, the concentration of NaOH is 2g / L, the concentration of KF is 1g / L, and the concentration of TiO 2 The concentration of nanoparticles is 2-4 g / L.
[0015] Furthermore, in step S2, the duration of the two ultrasonic treatments is 5 to 20 minutes.
[0016] Furthermore, in step S3, the micro-arc oxidation treatment is carried out under the following conditions: a double pulse constant current mode is adopted, and a forward current density of 5 to 10 A / dm 2 , duty cycle 10-30%, pulse frequency 300-500Hz; silicate alkaline electrolyte temperature is 25-35°C, and micro-arc oxidation reaction time is 5-20min.
[0017] Furthermore, in step S3, the magnesium alloy sample after the micro-arc oxidation treatment is rinsed with deionized water.
[0018] A highly wear-resistant micro-arc oxidation film layer on the surface of a magnesium alloy prepared by any of the above preparation methods.
[0019] The beneficial effects of the present invention are as follows:
[0020] 1. The present invention adds nano-TiO 2 particles, and the magnesium alloy was treated by micro-arc oxidation, TiO 2 Due to its good adsorption, it can adsorb particles in the electrolyte during the micro-arc oxidation reaction and distribute them around the micropores of the film layer, reducing the porosity of the film surface and increasing its density, thereby greatly improving its wear resistance. This improvement is of great significance for extending the service life of magnesium alloy parts, especially in high wear environments.
[0021] 2. The present invention limits the specific concentration of each component in the silicate alkaline electrolyte, making the electrolyte preparation more scientific and reasonable, especially the present invention adds TiO 2 The concentration of nanoparticles is limited to 2-8 g / L, which can avoid 2 Too high a concentration of nanoparticles causes agglomeration and forms larger particle clusters, which leads to uneven deposition on the surface of the magnesium alloy and reduces the overall quality of the film. 2 The particles may form a barrier layer near the electrode, hindering the flow of current, making it difficult for the micro-arc oxidation reaction to proceed effectively, thereby prolonging the treatment time and reducing the treatment efficiency. 2 The concentration of nanoparticles is too low, so their dispersibility and activity in the electrolyte are insufficient to significantly improve the microstructure and performance of the surface film layer of the magnesium alloy, and the effect of improving the wear resistance is not obvious.
[0022] 3. The present invention can not only remove the oxide layer and other impurities on the surface of the sample by grinding and polishing the magnesium alloy, but also ensure the surface flatness and smoothness of the sample, provide ideal starting conditions for subsequent micro-arc oxidation treatment, and help improve the quality and performance of the final film layer.
[0023] 4. The present invention adopts a double pulse constant current mode for micro-arc oxidation treatment, which can complete the treatment process in a shorter time while maintaining high energy efficiency. At the same time, by strictly controlling the treatment temperature, time and electrical parameters, not only the treatment efficiency is improved, but also the stability and consistency of the film formation are ensured, and the uncertainty caused by fluctuations in process parameters is reduced.
[0024] 5. The whole preparation process of the present invention pays attention to environmental protection measures, such as using deionized water and anhydrous ethanol for cleaning, and finally rinsing the treated magnesium alloy sample with deionized water, which not only ensures the cleanliness of the sample, but also meets the requirements of green manufacturing. At the same time, the method is simple and easy to implement, low cost, easy to industrialize and popularize, and has good economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 11 is the XRD spectrum of the micro-arc oxidation film in Examples 1 to 4 and Comparative Example 1.
[0026] Figure 2 (a) and (b) are the surface and cross-sectional morphologies of the micro-arc oxidation film in Comparative Example 1, respectively.
[0027] Figure 3 (a) and (b) are the surface and cross-sectional morphologies of the micro-arc oxidation film in Example 1, respectively.
[0028] Figure 4 (a) and (b) are the surface and cross-sectional morphologies of the micro-arc oxidation film in Example 2, respectively.
[0029] Figure 5 (a) and (b) are the surface and cross-sectional morphologies of the micro-arc oxidation film in Example 3, respectively.
[0030] Figure 6 (a) and (b) are the surface and cross-sectional morphologies of the micro-arc oxidation film in Example 4, respectively.
[0031] Figure 7 (a) to (f) are three-dimensional morphology images of the substrate and the micro-arc oxidation film prepared in Comparative Example 1, Example 1, Example 2, Example 3, and Example 4 after wear test under laser confocal microscope.
[0032] Figure 8 It is a statistical diagram of the wear volume of the micro-arc oxidation film in the substrate and comparative example 1, example 1, example 2, example 3, and example 4.
[0033] Fig. 9 (a) and (b) are the macroscopic and microscopic cross-sectional morphologies of the substrate after wear test, respectively.
[0034] Fig.10 (a) and (b) are respectively the macroscopic and microscopic cross-sectional morphologies of the micro-arc oxidation film in Comparative Example 1 after the wear test.
[0035] Fig.11 (a) and (b) are respectively the macroscopic and microscopic cross-sectional morphologies of the micro-arc oxidation film layer in Example 1 after the wear test.
[0036] Fig.12 (a) and (b) are respectively the macroscopic and microscopic cross-sectional morphologies of the micro-arc oxidation film layer in Example 2 after the wear test.
[0037] Fig.13 (a) and (b) are respectively the macroscopic and microscopic cross-sectional morphologies of the micro-arc oxidation film in Example 3 after the wear test.
[0038] Fig.14 (a) and (b) are respectively the macroscopic and microscopic cross-sectional morphologies of the micro-arc oxidation film in Example 4 after the wear test. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.
[0040] Example 1
[0041] The method for preparing a highly wear-resistant micro-arc oxidation film on the surface of a magnesium alloy described in this embodiment comprises the following steps:
[0042] S1. Magnesium alloy pretreatment: Cut the AZ91D magnesium alloy into a cuboid with a size of 10mm×10mm×3mm, and drill a hole with a diameter of 2mm at the center of the upper surface of the AZ91D magnesium alloy block. Use 800# and 1000# sandpaper to grind the AZ91D magnesium alloy block with holes, and then use a metallographic sample polishing machine to grind and polish until the surface of the block is as smooth as a mirror. Rinse the polished AZ91D magnesium alloy block with flowing deionized water, then rinse with flowing anhydrous ethanol, and finally dry it with a fan and put it into a clean sample storage bag for use.
[0043] S2. Prepare silicate alkaline electrolyte: At room temperature, weigh Na 2 SiO 3 , KF and NaOH were dissolved in deionized water and vibrated with an ultrasonic device for 10 min until they were completely dissolved before adding TiO 2 The nanoparticles were shaken for 10 min using an ultrasonic instrument until they were completely dispersed to obtain a silicate alkaline electrolyte. 2 SiO 3 The concentration is 10g / L, the concentration of NaOH is 2g / L, the concentration of KF is 1g / L, and the concentration of TiO 2 The concentration is 2g / L.
[0044] S3. Micro-arc oxidation treatment: stainless steel was used as cathode and the pretreated AZ91D magnesium alloy sample was used as anode in silicate alkaline electrolyte. Double pulse constant current mode was adopted with a forward current density of 4A / dm 2 , duty cycle 20%, pulse frequency 400 Hz, silicate alkaline electrolyte temperature 25 ~ 35 ℃, micro-arc oxidation reaction time is 15min, after the end, use deionized water to rinse the AZ91D magnesium alloy sample after micro-arc oxidation treatment, and finally use a fan to dry it, that is, a high wear-resistant micro-arc oxidation film layer is formed on the AZ91D magnesium alloy sample.
[0045] Example 2
[0046] The method for preparing a highly wear-resistant micro-arc oxidation film on the surface of a magnesium alloy described in this embodiment comprises the following steps:
[0047] S1. Magnesium alloy pretreatment: Cut the AZ91D magnesium alloy into a cuboid with a size of 10mm×10mm×3mm, and drill a hole with a diameter of 2mm at the center of the upper surface of the AZ91D magnesium alloy block. Use 800# and 1000# sandpaper to grind the AZ91D magnesium alloy block with holes, and then use a metallographic sample polishing machine to grind and polish until the surface of the block is as smooth as a mirror. Rinse the polished AZ91D magnesium alloy block with flowing deionized water, then rinse with flowing anhydrous ethanol, and finally dry it with a fan and put it into a clean sample storage bag for use.
[0048] S2. Prepare silicate alkaline electrolyte: At room temperature, weigh Na 2 SiO 3 , KF and NaOH were dissolved in deionized water and vibrated with an ultrasonic device for 10 min until they were completely dissolved before adding TiO 2 The nanoparticles were shaken for 10 min using an ultrasonic instrument until they were completely dispersed to obtain a silicate alkaline electrolyte. 2 SiO 3 The concentration is 10g / L, the concentration of NaOH is 2g / L, the concentration of KF is 1g / L, and the concentration of TiO 2 The concentration is 4g / L.
[0049] S3. Micro-arc oxidation treatment: stainless steel was used as cathode and the pretreated AZ91D magnesium alloy sample was used as anode in silicate alkaline electrolyte. Double pulse constant current mode was adopted with a forward current density of 4A / dm 2 , duty cycle 20%, pulse frequency 400 Hz, silicate alkaline electrolyte temperature 25 ~ 35 ℃, micro-arc oxidation reaction time is 15min, after the end, use deionized water to rinse the AZ91D magnesium alloy sample after micro-arc oxidation treatment, and finally use a fan to dry it, that is, a high wear-resistant micro-arc oxidation film layer is formed on the AZ91D magnesium alloy sample.
[0050] Example 3
[0051] The method for preparing a highly wear-resistant micro-arc oxidation film on the surface of a magnesium alloy described in this embodiment comprises the following steps:
[0052] S1. Magnesium alloy pretreatment: Cut the AZ91D magnesium alloy into a cuboid with a size of 10mm×10mm×3mm, and drill a hole with a diameter of 2mm at the center of the upper surface of the AZ91D magnesium alloy block. Use 800# and 1000# sandpaper to grind the AZ91D magnesium alloy block with holes, and then use a metallographic sample polishing machine to grind and polish until the surface of the block is as smooth as a mirror. Rinse the polished AZ91D magnesium alloy block with flowing deionized water, then rinse with flowing anhydrous ethanol, and finally dry it with a fan and put it into a clean sample storage bag for use.
[0053] S2. Prepare silicate alkaline electrolyte: At room temperature, weigh Na 2 SiO 3 , KF and NaOH were dissolved in deionized water and vibrated with an ultrasonic device for 10 min until they were completely dissolved before adding TiO 2 The nanoparticles were shaken for 10 min using an ultrasonic instrument until they were completely dispersed to obtain a silicate alkaline electrolyte. 2 SiO 3 The concentration is 10g / L, the concentration of NaOH is 2g / L, the concentration of KF is 1g / L, and the concentration of TiO 2 The concentration is 6g / L.
[0054] S3. Micro-arc oxidation treatment: stainless steel was used as cathode and the pretreated AZ91D magnesium alloy sample was used as anode in silicate alkaline electrolyte. Double pulse constant current mode was adopted with a forward current density of 4A / dm 2 , duty cycle 20%, pulse frequency 400 Hz, silicate alkaline electrolyte temperature 25 ~ 35 ℃, micro-arc oxidation reaction time is 15min, after the end, use deionized water to rinse the AZ91D magnesium alloy sample after micro-arc oxidation treatment, and finally use a fan to dry it, that is, a high wear-resistant micro-arc oxidation film layer is formed on the AZ91D magnesium alloy sample.
[0055] Example 4
[0056] The method for preparing a highly wear-resistant micro-arc oxidation film on the surface of a magnesium alloy described in this embodiment comprises the following steps:
[0057] S1. Magnesium alloy pretreatment: Cut the AZ91D magnesium alloy into a cuboid with a size of 10mm×10mm×3mm, and drill a hole with a diameter of 2mm at the center of the upper surface of the AZ91D magnesium alloy block. Use 800# and 1000# sandpaper to grind the AZ91D magnesium alloy block with holes, and then use a metallographic sample polishing machine to grind and polish until the surface of the block is as smooth as a mirror. Rinse the polished AZ91D magnesium alloy block with flowing deionized water, then rinse with flowing anhydrous ethanol, and finally dry it with a fan and put it into a clean sample storage bag for use.
[0058] S2. Prepare silicate alkaline electrolyte: At room temperature, weigh Na 2 SiO 3 , KF and NaOH were dissolved in deionized water and vibrated with an ultrasonic device for 10 min until they were completely dissolved before adding TiO 2 The nanoparticles were shaken for 10 min using an ultrasonic instrument until they were completely dispersed to obtain a silicate alkaline electrolyte. 2 SiO 3 The concentration is 10g / L, the concentration of NaOH is 2g / L, the concentration of KF is 1g / L, and the concentration of TiO 2 The concentration is 8g / L.
[0059] S3. Micro-arc oxidation treatment: stainless steel was used as cathode and the pretreated AZ91D magnesium alloy sample was used as anode in silicate alkaline electrolyte. Double pulse constant current mode was adopted with a forward current density of 4A / dm 2 , duty cycle 20%, pulse frequency 400 Hz, silicate alkaline electrolyte temperature 25 ~ 35 ℃, micro-arc oxidation reaction time is 15min, after the end, use deionized water to rinse the AZ91D magnesium alloy sample after micro-arc oxidation treatment, and finally use a fan to dry it, that is, a high wear-resistant micro-arc oxidation film layer is formed on the AZ91D magnesium alloy sample.
[0060] Comparative Example 1
[0061] In order to verify the TiO 2 For the improvement of the organization, structure and performance of the micro-arc oxidation film, this comparative example does not add TiO 2 Specifically, the method for preparing the micro-arc oxidation film on the surface of the magnesium alloy comprises the following steps:
[0062] S1. Magnesium alloy pretreatment: Cut the AZ91D magnesium alloy into a cuboid with a size of 10mm×10mm×3mm, and drill a hole with a diameter of 2mm at the center of the upper surface of the AZ91D magnesium alloy block. Use 800# and 1000# sandpaper to grind the AZ91D magnesium alloy block with holes, and then use a metallographic sample polishing machine to grind and polish until the surface of the block is as smooth as a mirror. Rinse the polished AZ91D magnesium alloy block with flowing deionized water, then rinse with flowing anhydrous ethanol, and finally dry it with a fan and put it into a clean sample storage bag for use.
[0063] S2. Prepare silicate alkaline electrolyte: At room temperature, weigh Na 2 SiO 3 , KF and NaOH were dissolved in deionized water and oscillated using an ultrasonic device for 10 min until they were completely dissolved to obtain a silicate alkaline electrolyte. 2 SiO 3 The concentration is 10g / L, the concentration of NaOH is 2g / L, and the concentration of KF is 1g / L.
[0064] S3. Micro-arc oxidation treatment: stainless steel was used as cathode and the pretreated AZ91D magnesium alloy sample was used as anode in silicate alkaline electrolyte. Double pulse constant current mode was adopted with a forward current density of 4A / dm 2 , duty cycle 20%, pulse frequency 400 Hz, silicate alkaline electrolyte temperature 25 ~ 35 ℃, micro-arc oxidation reaction time is 15min, after the end, use deionized water to rinse the AZ91D magnesium alloy sample after micro-arc oxidation treatment, and finally use a fan to dry it, that is, a high wear-resistant micro-arc oxidation film layer is formed on the AZ91D magnesium alloy sample.
[0065] XRD was used to analyze the phase composition of the film. Figure 1 The XRD spectra of the micro-arc oxidation film in Examples 1 to 4 and Comparative Example 1 show that the phases in the film mainly include MgO, Mg, MgSiO 3 and TiO 2 etc., where Mg comes from the AZ91D magnesium alloy matrix, MgO, MgSiO 3 It is formed during the micro-arc oxidation reaction, and as TiO 2 With the increase of TiO 2 With the addition of TiO, the thickness increases, and X-rays cannot easily penetrate the film layer to detect the matrix. 2 , it can be seen that TiO 2 Already entered the film layer through deposition.
[0066] Figure 2(a) and (b) are the surface morphology and cross-sectional morphology of the micro-arc oxidation film in Comparative Example 1, respectively. Figure 3 (a) and (b) are the surface morphology and cross-sectional morphology of the micro-arc oxidation film in Example 1, respectively. Figure 4 (a) and (b) are the surface morphology and cross-sectional morphology of the micro-arc oxidation film in Example 2, respectively. Figure 5 (a) and (b) are the surface morphology and cross-sectional morphology of the micro-arc oxidation film in Example 3, respectively. Figure 6 (a) and (b) are the surface morphology and cross-sectional morphology of the micro-arc oxidation film in Example 4, respectively. It can be seen that without adding TiO 2 When the film layer is added, there are more micropores and cracks on the surface, the porosity is larger, there are fewer disc-shaped substances, which are not tightly combined with each other, and the density of the film layer is low. 2 After that, the disc-shaped substances in the film increase, the defects are less, and the TiO 2 During the reaction, it enters the membrane layer and disperses around the micropores, reducing the surface porosity and improving the density of the membrane layer.
[0067] Energy dispersive spectrometer (EDS) was used to analyze the elemental composition of the micro-arc oxidation film layers in Examples 1 to 4 and Comparative Example 1. Table 1 is an EDS quantitative analysis table of the micro-arc oxidation film layers in Examples 1 to 4 and Comparative Example 1.
[0068] Table 1 EDS quantitative analysis table of micro-arc oxidation film in Examples 1 to 4 and Comparative Example 1
[0069] Sample O Mg Al Si Ti Comparative Example 1 52.50 37.71 2.44 7.35 - Example 1 57.78 30.86 3.09 7.53 0.74 Example 2 56.79 29.88 3.83 8.02 1.47 Example 3 53.64 34.92 2.32 6.78 2.34 Example 4 57.21 26.68 5.15 7.46 3.51
[0070] It can be seen from Table 1 that different TiO 2 The film prepared by micro-arc oxidation reaction at low concentrations mainly contains O, Mg, Al, Si, and Ti, and the content of Ti element increases with the concentration of TiO in the electrolyte. 2 The concentration increases with the increase of TiO 2 Participated in it.
[0071] Wear test: The friction test is carried out on the sample using a friction and wear tester. The friction principle between the ball and the disk and the microcomputer automatic control technology are used to apply the load to the sample surface. The friction process is amplified and converted to calculate the friction coefficient curve. Before starting the friction and wear test, the equipment needs to be debugged. After the debugging is completed, the sample is placed on the test table and the clamp is tightened to prevent movement during the test. A Si with a diameter of 4 mm is used. 3 N 4For the friction pair, pay attention to tightening the joints when installing the friction pair to prevent loosening during the long test process and affect the test results. After installation, adjust the friction pair to 2mm above the sample and fix the position. After the sample and the friction pair are installed, gently turn the instrument motor to observe whether the sliding track falls on the surface of the sample. After preparation, conduct friction and wear tests. Select a load of 5N, a friction time of 15min, a length of 5mm, and a frequency of 2Hz. During the test, try to avoid touching the sample, friction and wear equipment, and the test bench to avoid shaking that affects the test results.
[0072] Laser confocal microscopy was used to characterize and test the film after wear test. Figure 7 As shown, the average size of the wear scar of each film layer is obtained from the three-dimensional morphology diagram, and Table 2 is a comparison table of the average size of the wear scars of the substrate and the micro-arc oxidation films in Examples 1 to 4 and Comparative Example 1 after the wear test. The volume of wear of each film layer is calculated based on the data in Table 2, so as to compare the wear resistance of the micro-arc oxidation films. Figure 8 The wear volume statistics of the micro-arc oxidation film in Examples 1 to 4 and Comparative Example 1 are shown in FIG. Figure 7 (a)~(e) and Figure 8 With the development of TiO 2 As the particle content increases, the depth of the wear scar decreases first and then increases. 2 When the wear scar depth is the lowest, the wear volume is the smallest, which is 0.1027mm 3 , and from the three-dimensional morphology, it is relatively smooth, without obvious protrusions and pits. 2 Therefore, nano-TiO 2 The particles can modify the micro-arc oxidation film to make it have higher wear resistance.
[0073] Table 2 Comparison table of average wear scar sizes of micro-arc oxidation films of substrates, examples 1 to 4, and comparative example 1
[0074]
[0075]
[0076] After the wear test, the macroscopic and microscopic morphologies of the micro-arc oxidation films in Examples 1 to 4 and Comparative Example 1 were observed using SEM. Fig. 9 (a) and (b) are the macroscopic and microscopic morphologies of the AZ91D magnesium alloy substrate after wear test, respectively.
[0077] Fig.10 (a) and (b) are respectively the macroscopic and microscopic morphologies of the micro-arc oxidation film in Comparative Example 1 after the wear test. Fig.11(a) and (b) are respectively the macroscopic and microscopic morphologies of the micro-arc oxidation film in Example 1 after the wear test. Fig.12 (a) and (b) are respectively the macroscopic and microscopic morphologies of the micro-arc oxidation film in Example 2 after the wear test. Fig.13 (a) and (b) are respectively the macroscopic and microscopic morphologies of the micro-arc oxidation film in Example 3 after the wear test. Fig.14 (a) and (b) are respectively the macroscopic and microscopic morphologies of the micro-arc oxidation film in Example 4 after the wear test. It can be seen that the addition of TiO 2 After that, it is helpful to reduce the disc-shaped objects and micropores on the surface of the film. 2 The surface of the nanostructured carbon nanotubes has good adsorption properties. The particles in the electrolyte are adsorbed and brought into the membrane layer under the action of the electric field. After participating in the micro-arc oxidation reaction, they are distributed around the micropores, reducing the surface porosity and improving the density of the membrane layer.
[0078] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.
Claims
1. A method for preparing a highly wear-resistant micro-arc oxidation film on the surface of a magnesium alloy, characterized in that: The following steps are involved: S1. Pretreatment of the magnesium alloy substrate: grinding and polishing the magnesium alloy substrate, and then cleaning and drying; S2. Prepare a silicate alkaline electrolyte: Na2SiO3, KF and NaOH were dissolved in deionized water at room temperature, and then the TiO2 nanoparticles were added after ultrasonic treatment until they were completely dissolved, and the ultrasonic treatment was continued until the TiO2 nanoparticles were uniformly dispersed in the deionized water to obtain a silicate alkaline electrolyte; S3. Micro-arc oxidation treatment: stainless steel is used as cathode and the pretreated magnesium alloy substrate is used as anode and placed in a silicate alkaline electrolyte. After micro-arc oxidation treatment, it is rinsed and dried to form a highly wear-resistant micro-arc oxidation film layer on the magnesium alloy sample.
2. The preparation method according to claim 1, characterized in that: The magnesium alloy in step S1 is AZ91D magnesium alloy.
3. The preparation method according to claim 1, characterized in that: In step S1, the specific steps of cleaning are: using deionized water and anhydrous ethanol to rinse the polished magnesium alloy block in sequence.
4. The preparation method according to claim 1, characterized in that: In the silicate alkaline electrolyte, the concentration of Na2SiO3 is 5-10 g / L, the concentration of NaOH is 1-3 g / L, the concentration of KF is 0.5-2 g / L, and the concentration of TiO2 nanoparticles is 2-8 g / L.
5. The preparation method according to claim 4, characterized in that: In the silicate alkaline electrolyte, the concentration of Na2SiO3 is 10 g / L, the concentration of NaOH is 2 g / L, the concentration of KF is 1 g / L, and the concentration of TiO2 nanoparticles is 2-4 g / L.
6. The preparation method according to claim 1, characterized in that: In step S2, the duration of the two ultrasonic treatments is 5 to 20 minutes.
7. The preparation method according to claim 1, characterized in that: In step S3, the micro-arc oxidation treatment conditions are: using a double pulse constant current mode, with a forward current density of 5 to 10 A / dm 2 , duty cycle 10-30%, pulse frequency 300-500Hz; silicate alkaline electrolyte temperature is 25-35°C, and micro-arc oxidation reaction time is 5-20min.
8. The preparation method according to claim 1, characterized in that: In step S3, the magnesium alloy sample after the micro-arc oxidation treatment is rinsed with deionized water.
9. A highly wear-resistant micro-arc oxidation film on the surface of a magnesium alloy prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing wear-resistant black ceramic film layer on surface of magnesium alloy
CN118186536A
Cited By
High-corrosion-resistance and wear-resistance micro-arc oxidation film and preparation method thereof
CN122503922A